The Mediating Role of Organizational Culture in the Relationship Between Leadership Frameworks and Job Satisfaction Among Police Officers in Palestine - Taysir Yousef Diab Ostaali
Employees see low job satisfaction as one of the negative phenomena that most governmental and non-governmental organizations and institutions, including the police institution, suffer from. In this regard, the study aimed to reveal the role of organizational culture in the relationship between the application of leadership frameworks and job satisfaction among Palestinian police officers in the West Bank of Palestine. To achieve the study's objectives, The analytical descriptive approach was employed in this study to ensure a thorough and comprehensive exploration of the data, reveal patterns and trends, test hypotheses, and derive valid conclusions with practical applications. The study community included all Palestinian police officers in the West Bank, and 400 questionnaires were distributed. Out of these, 356 valid questionnaires were used for analysis, resulting in an 89% response rate. To achieve the study's objectives and analyse its hypotheses, this study used a questionnaire consisting of 67 items distributed on four sections, as well as five expressions that measure demographic variables. AMOS structural equation models and SPSS software were used. The theoretical model of this study is based on organizational culture theory by Denison and Mishra (1995), Bolman and Deal's (1991) theory, and furthermore, this study indicated the prominent job satisfaction theories, such as Maslow theory, and the Alderfer theory. Additionally, Herzberg's dual-factor theory. The findings from the structural modelling equation path analysis revealed positive relationships between leadership frameworks and job satisfaction, organizational culture and job satisfaction, and leadership frameworks and organizational culture. Moreover, the study highlighted a significant indirect effect of leadership frameworks on job satisfaction through organizational culture among police officers in the West Bank. Based on these results, several recommendations were proposed. Firstly, there is a need to focus on improving wages and ensuring their consistency, considering linking them to the cost-of-living rates. Secondly, implementing an effective system of material and moral incentives for Palestinian police officers is essential. Additionally, supporting the Ministry of Interior and police leadership in adopting and implementing laws that increase the level of satisfaction among police officers would contribute to improving their overall performance.